Pelatihan dan Pendampingan Pengimplementasian Alat Peraga Kopermatik Bagi Guru Sekolah Dasar - Sri Subarinah; Sudi Prayitno; Dwi Novitasari; Junaidi Junaidi; Tabita Wahyu Triutami (Rengganis Jurnal Pengabdian Masyarakat, 2023)
Elementary school teachers in Cluster II Gerung District are still very rare in using visual aids in teaching mathematical concepts. As a result, students have difficulty understanding abstract mathematical material, while elementary school children are still at the concrete thinking stage. Therefore, this activity aims to train and assist elementary school teachers in Cluster II Gerung District in implementing Kopermatik teaching aids (Mathematics Game Boxes) for classroom learning. The training method includes discussions and demonstrations in making and using Kopermatik teaching aids as well as simulations in utilizing the Kopermatik teaching aids. This service activity was carried out at an elementary school in Gerung District, with 18 elementary school teachers participating. The results of the data analysis show that the teachers participating in the activity: (1) are enthusiastic and communicative in participating in the activity, (2) can practice making Kopermatik mathematics teaching aids with quite good and varied results, (3) give positive response to the usefulness of Kopermatik teaching aids, and (4) more than 65% of teachers were able to answer each evaluation question correctly